Pregnancy after percutaneous ethanol sclerotherapy for uterine arteriovenous fistula: Case report. Issue 11 (15th August 2021) - Xu, Lei; Wang, Yu; Yuan, Hai; Zhang, Shiyi; Wu, Xuejun; Huo, Ran
Abstract: Uterine arteriovenous fistula is a rare but life‐threatening gynecologic entity. Meanwhile, long‐term radiation exposure will do serious harm to doctors' health. So we improve the operation method to reduce the radiation exposure time. The patient, a 24‐years‐old woman with a history of dilation and curettage, had long‐term menorrhagia and anemia. Uterine arteriovenous fistula was confirmed by ultrasonography and computed tomography angiograph. Percutaneous anhydrous ethanol sclerotherapy was performed under the guidance of the X‐ray imaging. The patient was followed up for 2 years without recurrence and had normal menstruation. Recently, she is successfully pregnant again. Percutaneous anhydrous ethanol sclerotherapy is a new option treating uterine arteriovenous fistula, which can greatly shorten the irradiation time and reduce the recurrence rate and has no obvious adverse effect on fertility.